2017
DOI: 10.3390/su9111954
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of TRMM Multi-Satellite Precipitation Products With Reference to Rain Gauge Observations in Hunza River Basin, Karakoram Range, Northern Pakistan

Abstract: Abstract:The performance evaluation of satellite-based precipitation products at local and regional scales is crucial for modification in satellite-based precipitation retrieval algorithms, as well as for the provision of guidance during the selection of substitute precipitation data. This study evaluated the performances of three Tropical Rainfall Measuring Mission (TRMM) Multi-satellite Precipitation Analysis (TMPA) products (3B42V6, 3B42RT and 3B42V7) with a reference to rain gauge observations in the Hunza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 31 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…Overall, both of the TMPA products underestimated rainfall across the entire study period. However, 3B72V7 performed better than 3B42RT, which agrees with the finding of various recently conducted studies [53,54,57,77,78] in Pakistan. Further, our study strengthens the fact that the performance of TMPA products depends upon seasons and various timescales [16,79].…”
Section: Discussionsupporting
confidence: 91%
“…Overall, both of the TMPA products underestimated rainfall across the entire study period. However, 3B72V7 performed better than 3B42RT, which agrees with the finding of various recently conducted studies [53,54,57,77,78] in Pakistan. Further, our study strengthens the fact that the performance of TMPA products depends upon seasons and various timescales [16,79].…”
Section: Discussionsupporting
confidence: 91%
“…Krakauer et al [4] compared different precipitation datasets with the available stations' data over the Indus Basin and found the TRMM dataset to perform best among the remote sensing datasets. Similarly, Ali et al [43] evaluated the TRMM Multi-satellite Precipitation Analysis (TMPA) precipitation products (3B42V6, 3B42V7, and 3B42RT) with gauge stations over the Hunza Basin in Karakoram Mountainous range. They also found 3B42V7 reasonably better than the other two products.…”
Section: Model Validationmentioning
confidence: 99%
“…Several studies have reported a very low amount of annual precipitation in UIB quantified from different products [e.g., 300 mm based on TRMM in Bookhagen and Burbank (2010) and Immerzeel et al (2009Immerzeel et al ( , 2010]. Many previous studies have discussed the applicability, usefulness, calibration, and limitations of TRMM dataset in Himalaya-Karakorum-Hindu Kush region (Ali et al 2017;Anjum et al 2016Anjum et al , 2018Burbank 2006, 2010;Cheema and Bastiaanssen 2012;Dahri et al 2016;Khan et al 2018;Khan et al 2014;Maggioni et al 2016). The differences in our and their results owing to different coverage of study area, periods, and meteorological stations applied in the analysis.…”
Section: A Spatiotemporal Distribution and Performance Of Gridded Precipitationmentioning
confidence: 99%